Early post-operative mobilisation to prevent Venous Thromboembolism in laparoscopic surgery: a clinical audit - Asma Burney; Zafar Jawed, Saba; Burney, Mariah (Journal of the Pakistan Medical Association, 2026)
Venous thromboembolism (VTE) is a recognised post-operative complication following laparoscopic surgery. For its prevention, the American College of Chest Physicians (ACCP) and the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES) recommend various prophylactic measures based on the patient’s risk, calculated using the Caprini and Rogers scoring systems. Of the proposed recommendations, early mobilisation is a practical and cost-effective VTE prevention strategy in a resource-limited setting like ours. This audit aimed to assess the risk of venous thromboembolism in patients undergoing laparoscopic surgeries and their compliance to early post-operative mobilisation. The key objective was to identify and address the limiting factors to improve patient outcome. Using the Caprini score, the VTE risk for 30 post-laparoscopy patients was assessed and their mobilisation times recorded. The results revealed that while 53% of the patients were at “moderate risk”, making early mobilisation crucial, only 7% mobilised within the recommended two to three hours. The majority (63%) did not mobilise until more than six hours post-surgery. These findings highlight the need for improved compliance with early mobilisation protocols, adherence to which can effectively reduce the prevalence of VTE, leading to enhanced patient outcomes and shorter hospital stays. Keywords: Early mobilisation, Venous thromboembolism, Laparoscopic surgery, Clinical audit.